Spontaneous coronary artery dissection in women in the generative period: clinical characteristics, treatment, and outcome—a systematic review and meta-analysis - Apostolović, Svetlana; Ignjatović, Aleksandra; Stanojević, Dragana; Radojković, Danijela Djordjević; Nikolić, Miroslav; Milošević, Jelena; Filipović, Tamara; Kostić, Katarina; Miljković, Ivana; Djoković, Aleksandra; Krljanac, Gordana; Mehmedbegović, Zlatko; et al. (Frontiers in Cardiovascular Medicine, 2024)
Introduction Spontaneous coronary artery dissection (SCAD) is a non-traumatic and non-iatrogenic separation of the coronary arterial wall. Materials and methods This systematic review and meta-analysis is reported following the PRISMA guidelines and is registered in the PROSPERO database. A literature search was focused on female patients in generative period (16–55 of age) with acute coronary syndrome (ACS) caused by SCAD, and comparison from that database NP-SCAD (spontaneous coronary artery dissection in non pregnant women) and P-SCAD (spontaneous coronary artery dissection in pregnant women). Results 14 studies with 2,145 females in the generative period with ACS caused by SCAD were analyzed. The median age was 41 years (33.4–52.3 years). The most common risk factor was previous smoking history in 24.9% cases. The most common clinical presentation of ACS was STEMI in 47.4%. Conservative treatment was reported in 41.1%. PCI was performed in 32.7%, and 3.8% of patients had CABG surgery. LAD was the most frequently affected (50.5%). The prevalence of composite clinical outcomes including mortality, non-fatal MI and recurrent SCAD was 3.3% (95% CI: 1.4–5.1), 37.7% (95% CI: 1.9–73.4) and 15.2% (95% CI: 9.1–21.3) of patients. P-SCAD compared to NP-SCAD patients more frequently had STEMI (OR = 3.16; 95% CI: 2.30–4.34; I2 = 64%); with the left main and LAD more frequently affected [(OR = 14.34; 95% CI: 7.71–26.67; I2 = 54%) and (OR = 1.57; 95% CI: 1.06–2.32; I2 = 23%)]; P-SCAD patients more frequently underwent CABG surgery (OR = 6.29; 95% CI: 4.08–9.70; I2 = 0%). NP-SCAD compared to P-SCAD patients were more frequently treated conservatevly (OR = 0.61; 95% CI: 0.37–0.98; I2 = 0%). In P-SCAD compared to NP-SCAD mortality rates (OR = 1.13; 95% CI: 0.06–21.16; I2 = not applicable) and reccurence of coronary artery dissection (OR = 2.54; 95% CI: 0.97–6.61; I2 = 0%) were not more prevalent. Conclusion The results of this meta-analysis indicated that patients with P-SCAD more frequently had STEMI, and events more frequently involved left main and LAD compared to NP-SCAD patients. Women with NP-SCAD were significantly more often treated conservatively compared to P-SCAD patients. P-SCAD compared to NP-SCAD patients did not have significantly higher mortality rates or recurrent coronary dissection.